2016
DOI: 10.1152/ajplung.00451.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of suplatast tosilate on acutely dissociated sensory and paratracheal ganglia neurons

Abstract: In this study, we investigated the effects of suplatast on acutely dissociated single neurons of sensory and paratracheal ganglia using a patch-clamp technique. Suplatast had little effect on various responses caused by capsaicin, acid, bradykinin, serotonin and adenosine 5'-triphosphate in rat sensory neurons. Suplatast, even at 10-3 M, also did not induce any current at various membrane potentials in rat and guinea pig paratracheal ganglia neurons. Further, acetylcholine- and bradykinin-induced depolarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…These results suggest that suplatast may not affect TRPV1 receptor functions. Together with our previous study [12], it is further suggested that suplatast may have no direct effect on the sensory neurons/fibers, at least the nociceptive neurons/fibers (C- and nociceptive Aδ-fibers).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These results suggest that suplatast may not affect TRPV1 receptor functions. Together with our previous study [12], it is further suggested that suplatast may have no direct effect on the sensory neurons/fibers, at least the nociceptive neurons/fibers (C- and nociceptive Aδ-fibers).…”
Section: Resultssupporting
confidence: 74%
“…However, the antitussive effect of suplatast does not appear to be due to the anti-allergic effect caused by Th2 cytokine inhibition. Recently, we found that in rat paratracheal ganglia neurons, suplatast inhibited postsynaptic nicotinic current, and in rat trigeminal ganglion (TG) neurons, suplatast had little effect on various responses caused by capsaicin, acid, bradykinin, serotonin, and adenosine 5’-triphosphate (ATP) [12]. Moreover, suplatast is known to inhibit histamine releases from the mast cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…As noted previously, compound S6 is suplatast, a known compound with anti-inflammatory activity [ 19 ], which has shown silent agonist activity in our present study. It has been proposed that at least the antitussive activity of suplatast may be due to its ability to function as a channel blocker of ganglionic (α3β4) nAChR [ 29 ], preventing afferent impulses to muscles associated with cough. Note that, while Zhou et al reported channel block with 100 µM suplatast, we observed inhibition of α3β4 receptors with an IC 50 of only 4.5 µM, and our data are consistent with a non-competitive mechanism of inhibition (i.e., channel block) since S6 inhibition was not surmountable by increasing ACh concentration.…”
Section: Discussionmentioning
confidence: 99%